New science of learning: Cognition, computers and collaboration in education - Khine, Myint Swe; Saleh, I. (Springer New York, 2010)
The earliest educational software simply transferred print material from the page to the monitor. Since then, the Internet and other digital media have brought students an ever-expanding, low-cost knowledge base and the opportunity to interact with minds around the globe while running the risk of shortening their attention spans, isolating them from interpersonal contact, and subjecting them to information overload. The New Science of Learning: Cognition, Computers and Collaboration in Education deftly explores the multiple relationships found among these critical elements in student's increasingly complex and multi-paced educational experience. Starting with instructor's insights into the cognitive effects of digital media a diverse range of viewpoints with little consensus this cutting-edge resource acknowledges the double-edged potential inherent in computer-based education and its role in shaping student's thinking capabilities. Accordingly, the emphasis is on strategies that maximize the strengths and compensate for the negative aspects of digital learning, including: Group cognition as a foundation for learning Metacognitive control of learning and remembering Higher education course development using open education resources Designing a technology-oriented teacher professional development model Supporting student collaboration with digital video tools Teaching and learning through social annotation practices The New Science of Learning: Cognition, Computers and Collaboration in Education brings emerging challenges and innovative ideas into sharp focus for researchers in educational psychology, instructional design, education technologies, and the learning sciences. © Springer Science+Business Media, LLC 2010. All rights reserved.